Compromised Primary Implant Stability - Queiroz, Thallita Pereira; Souza, Francisley Ávila [UNESP]; Okamoto, Roberta [UNESP]; Luvizuto, Eloa Rodrigues [UNESP]; Margonar, Rogerio; Garcia, Idelmo Rangel [UNESP]; Vieira, Eduardo Hochuli [UNESP] (Lippincott Williams & Wilkins, 2012)
The aim of this study was to evaluate implants installed with compromised primary stability associated or not with polylactide and polyglycolide copolymer (PLA/PGA). Two 0.4-mm overdrilled defects (3 mm in diameter and 6 mm long) were produced in the right tibia of 25 rabbits. Half of the defects were left untreated, and the other half was filled with PLA/PGA. Implants of 2.6 mm in diameter and 6 mm long were placed into all defects. Animals were killed at 5, 15, 40, and 60 postoperative days, and biomechanical analysis (torque-reverse), histomorphometry, and immunohistochemistry (osteoprotegerin, receptor activator of NFJB ligand [RANKL], osteocalcin, and collagen-1 [ COL- I] staining) were performed. All the implants achieved osseointegration. There were no statistically significant differences in the torque-reverse and in linear contact extension between bone tissue and implant surface and no statistically significant difference in osteoprotegerin, RANKL, osteocalcin, and collagen-1 expression between the studied groups in all studied periods (P > 0.05). We can conclude that osseointegration can occur in compromised primary implant stability situations, and the addition of PLA/PGA did not improve the osseointegration process in this experimental model.
Keywords: PLA/PGA; titanium implants; bone defect; animal model